Transcatheter aortic valve implantation in a young heart transplant recipient crossing the traditional boundaries - Ahmad, Khalil; Terkelsen, Christian Juhl; Terp, Kim Allan; Mathiassen, Ole Norling; Nørgaard, Bjarne Linde; Andersen, Henning Rud; Poulsen, Steen Hvitfeldt (Journal of Thoracic Disease, 2016)
Transcatheter aortic valve implantation (TAVI) is an established therapeutic alternative to surgical aortic valve replacement (SAVR) in high-risk or inoperable patients with symptomatic aortic valve stenosis. Hitherto, TAVI is not recommended in young and low-intermediate risk patients. However, TAVI may also serve as an alternative to SAVR in selected young patients, e.g., patients who have previously undergone multiple cardiac surgery procedures. We report a case of trans-femoral TAVI in a 25-year-old heart transplant (HTx) recipient with prior surgery for congenital heart disease.